Grafts of adenosine-releasing cells suppress seizures in kindling epilepsy - Huber, Alexander (The National Academy of Sciences, 2001)
Adenosine is an inhibitor of neuronal activity in the brain. The local release of adenosine from grafted cells was evaluated as an ex vivo gene therapy approach to suppress synchronous discharges and epileptic seizures. Fibroblasts were engineered to release adenosine by inactivating the adenosine-metabolizing enzymes adenosine kinase and adenosine deaminase. After encapsulation into semipermeable polymers, the cells were grafted into the brain ventricles of electrically kindled rats, a model of partial epilepsy. Grafted rats provided a nearly complete protection from behavioral seizures and a near-complete suppression of afterdischarges in electroencephalogram recordings, whereas the full tonic–clonic convulsions in control rats remained unaltered. Thus, the local release of adenosine resulting in adenosine concentrations <25 nM at the site of action is sufficient to suppress seizure activity and, therefore, provides a potential therapeutic principle for the treatment of drug-resistant partial epilepsies.